Günümüz sosyolojisinde modernleşme-sekülerleşme-din ilişkileri - Özay, Mehmet (My University, 2006)
Bu tez çalışmasında “günümüz sosyolojisinde modernleşme-sekülerleşme-din ilişkilerini” ele aldık. Bu bağlamda, din sosyolojisinin önemli bir araştırma konusu olan sekülerleşmeyi mevcut üç paradigma modelini inceledik. Modern dönemde yaşanan bir dizi toplumsal değişmeler, dinin toplumsal bağlamında ciddi kırılmaların yaşanıp yaşanmadığını sorgulamayı gerektirmiştir. Bir başka deyişle, çalışmanın çıkış noktasını, din olgusunun, yani Hıristiyanlığın “modern dünyanın başat unsuru olan Batı toplumlarında nasıl tezahür ettiği?” yönündeki temel sorumuz oluşturmaktadır. Bu bağlamda sekülerleşme-din ilişkisi, ancak kültürel anlam çerçevesinde bir açıklamaya tabi tutulabileceğinden çalışmamızda Batı toplumları üzerinde durulmuştur. Çalışmanın çeşitli bölümlerinde sosyal bir realite olan dinin çeşitli sosyal dinamiklerle arasındaki ilişkileri üzerinde durulmuştur. Çalışma giriş, dört ana başlık ve sonuç bölümlerinden oluşmaktadır. sosyoloji ve din ilişkisi ile, konunun tarihi perspektifi, dinin anlamı ve kurucu sosyologlarda din olgusunu ele aldık. Sekülerleşmenin sosyolojik temelleri başlığını taşıyan İkinci Bölüm’de değişme olgusu çeşitli açılımları ile değerlendirilmiş. Ayrıca modern-pre modern ayrımından yola çıkılarak din-modernleşme ilişkisi üzerinde ayrıntılı olarak durulmuştur. Çalışmamızın ana gövdesini oluşturan sekülerleşme paradigmaları Üçüncü Bölüm’de ele alınmıştır. Bu anlamda, tarihi gelişim itibariyle eski paradigma, yeni paradigma ve eklektik (neo) paradigma temel argümanları bağlamında incelenmiştir. Sekülerleşmeye yol açan faktörler içsel ve dışsal olmak üzere iki temel açılıma konu olmuştur. Bu bölümde, ayrıca, son dönemde öne çıkan ve dinin modern dünyada var olduğunun güçlü bir kanıtı olarak öne sürülen yeni dini hareketlere de değinme fırsatı bulduk. Dördüncü ve son bölümde ise günümüz sosyolojisinin, yani Batı’da sekülerleşme konusunu iki temel coğrafi etken bağlamında değerlendirmek amacıyla Amerika Birleşik Devletleri ve Avrupa arasında bir karşılaştırma yaptık.

The recognition of the importance of religion in contemporary modern societies causes to make more researches in the field of sociology of religion. The discipline has directed increased attention to the role of religion in modern socities. As a result of this fact, we deals with the relations between modernization-secularization-religion in contemporary sociology in this work. Secularization, which is a significant research topic in the field of sociology of religion, is deserved to be held in the context of paradigms, as varities of different standpoints. So we deal with this topic by the help of three significant paradigm models. Considerable social changes in the modern period need to make a study done whether religion has lost its societal significance and drained away or is still a fundamental aspiration for human beings. In another saying, as the starting point of this thesis, we pose a fundamental question “How religion, as a phenomenon, mainly Christianity, has occured in the Western societies which are the dominant driving force of modernity?”. Since the relations between secularization-religion are examined in cultural context we just study the situation in the West. We look at the relations between some social dynamics and religion, which is a social reality, under some different titles in the work. It includes introduction, four main chapters and result. Chapter 1 is general rather than specific as we focus on sub-topics, such as relations between sociology and religion, historical perspectives, some definitions of religion and how the founding fathers of sociology understand religion. Chapter 2 titled as the socilogical basis of secularization we examine social change in different aspects. Beyond that, modernity-religion relations are held in detail, starting from the differance between modern-pre modern. We indicates the relations between the paradigms of secularization named as old, new and eclectic (neo), which is the main topic of this work, in the context of history of sociology of religion in Chapter 3. We examine and emphasize a set of contrasts and similarities between them. The reasons of secularizations are examined as internal and external factors. Beyond that, we are concerned about NRM (New Religious Movements) which have been on the agenda in the last thirty years and have been accepted as an inevitable proof for the existence of sacred in modern life in western countries. Chapter 4, since the difference between two continents is very important in contemporary sociology of religion, we could not have overlooked this matter. It means that in the western world secularization is thought in two main context. On the one hand, in the context of the United States of America, on the other hand, in the context of Europe. We found to make a comparison between these two continent mainly.
Keywords: Din Sosyolojisi; Sosyoloji_Modernleşme